Study of counseling effectiveness on bullying in students - Handayani, Listy; Virdayanti, Fadya; Iwan, Putri; Israwati, Wa Ode; Riastami, Dilla Salsabilla S.; Ramadhan, Jimip Selahri; Rachma, Lula Nur (CORE JOURNAL, 2024)
Bullying in the school is aggressive behavior carried out repeatedly by students or groups of students in power towards other students who are more vulnerable, with the aim of hurting them. Globally, it showed that 32% of students worldwide have been victims of bullying. The prevalence of bullying cases in Indonesia was 41%. Meanwhile, in Kendari City there is no specific data regarding bullying. This research aimed to determine the effectiveness of counseling in increasing students' knowledge about bullying in Kendari City. The type of study was pre-experimental with a one-group pre-test post-test design.  The sample size of 18 students were selected by accidental Sampling in Class XI. Data was collected with used pre-test and post-test questionnaires. Data was processed and analyzed by epi info 7 application. A non-parametric statistical analysis, wilcoxon test used to analyze the data. The study founded that there was an increase in students' level of knowledge before and after the counseling was carried out. The statistical test results showed a p-value of 0.0114 < α (0.05), meaning there was a significant difference between students' knowledge before and after the counseling. Thus, it can be concluded that counseling is effective in increasing students' knowledge about bullying. Therefore, this research can be input for schools to strengthen bullying prevention programs by carrying out regular anti-bullying counseling with interesting and interactive methods at all grade levels in school and develop an anti-bullying team at school consisting of (teachers, counselors and other school staff).